The Impact of Rising Gold Prices on Financial Markets and the Rupiah Exchange Rate - Amel Rezkia Rachmat; Yulianah Yulianah; Aldy Nurdin; Dea Amanda Amelia; Pricilla Aprilia Putri; Agung Agustrianto (Advances in Community Services Research, 2026)
Purpose: This study aims to examine the influence of global gold price movements on Indonesia's financial market indicators, namely the Rupiah exchange rate and the Jakarta Composite Index (JCI), during the 2020–2026 period. Research Method: A quantitative associative approach was employed using monthly secondary time-series data collected from Investing.com, Bank Indonesia, and the Indonesia Stock Exchange. Multiple linear regression analysis was applied to assess the relationships among the variables. Results and Discussion: The findings reveal that global gold prices are associated with fluctuations in Indonesia's financial markets. The JCI model yielded an R-Square value of 0.620 with a Significance F value of 3.22 × 10⁻¹⁷, while the Rupiah exchange rate model produced an R-Square value of 0.373. Implications: These results highlight the importance of monitoring gold price volatility in investment decision-making and financial stability policies. Originality: This study simultaneously investigates the effects of global gold prices on both the Rupiah exchange rate and the JCI, providing evidence from Indonesia during the post-pandemic period.